Gene‐Based Meta‐Analysis of Genome‐Wide Association Study Data Identifies Independent Single‐Nucleotide Polymorphisms in ANXA6 as Being Associated With Systemic Lupus Erythematosus in Asian Populations. Issue 11 (November 2015) - Zhang, Jing; Zhang, Lu; Zhang, Yan; Yang, Jing; Guo, Mengbiao; Sun, Liangdan; Pan, Hai‐Feng; Hirankarn, Nattiya; Ying, Dingge; Zeng, Shuai; Lee, Tsz Leung; Lau, Chak Sing; et al.
Abstract : Objective: Previous genome‐wide association studies (GWAS), which were mainly based on single‐variant analysis, have identified many systemic lupus erythematosus (SLE) susceptibility loci. However, the genetic architecture of this complex disease is far from being understood. The aim of this study was to investigate whether using a gene‐based analysis may help to identify novel loci, by considering global evidence of association from a gene or a genomic region rather than focusing on evidence for individual variants. Methods: Based on the results of a meta‐analysis of 2 GWAS of SLE conducted in 2 Asian cohorts, we performed an in‐depth gene‐based analysis followed by replication in a total of 4, 626 patients and 7, 466 control subjects of Asian ancestry. Differential allelic expression was measured by pyrosequencing. Results: More than one‐half of the reported SLE susceptibility loci showed evidence of independent effects, and this finding is important for understanding the mechanisms of association and explaining disease heritability. ANXA6 was detected as a novel SLE susceptibility gene, with several single‐nucleotide polymorphisms (SNPs) contributing independently to the association with disease. The risk allele of rs11960458 correlated significantly with increased expression of ANXA6 in peripheral blood mononuclear cells from heterozygous healthy control subjects. Several other associated SNPs may also regulate ANXA6 expression, according to data obtained from public databases. Higher expression of ANXA6 in patients with SLE was also reported previously. Conclusion: Our study demonstrated the merit of using gene‐based analysis to identify novel susceptibility loci, especially those with independent effects, and also demonstrated the widespread presence of loci with independent effects in SLE susceptibility genes.